2004
DOI: 10.1111/j.1365-2141.2004.05025.x
|View full text |Cite
|
Sign up to set email alerts
|

Are there clinical phenotypes of homozygous sickle cell disease?

Abstract: Summary The distribution of clinical features was examined in subjects with homozygous sickle cell (SS) disease in the Jamaican Cohort Study to determine whether there is evidence of distinct clustering of symptoms or clinical phenotypes. A twofold model yielded groups that could be interpreted as painful crisis or leg ulcer phenotypes and 78% of patients were classified with 95% confidence into one of these. The painful crisis phenotype also manifested higher frequencies of dactylitis, meningitis/septicaemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 13 publications
5
45
2
1
Order By: Relevance
“…Sickle cell patients with leg ulcers constitute a relatively distinct sub-phenotype, characterized by less frequent hospitalizations for vaso-occlusive pain crisis [22,23], while they are prone to develop pulmonary hypertension [5,[24][25][26][27][28], suggesting that the two complications share a common pathophysiology. In a cohort of 20 SCD patients with leg ulcer who underwent right hearth catheterization for suspected pulmonary hypertension, 15 had confirmation of PAH (personal data, this cohort has been described in Mehari et al (2013) [24].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Sickle cell patients with leg ulcers constitute a relatively distinct sub-phenotype, characterized by less frequent hospitalizations for vaso-occlusive pain crisis [22,23], while they are prone to develop pulmonary hypertension [5,[24][25][26][27][28], suggesting that the two complications share a common pathophysiology. In a cohort of 20 SCD patients with leg ulcer who underwent right hearth catheterization for suspected pulmonary hypertension, 15 had confirmation of PAH (personal data, this cohort has been described in Mehari et al (2013) [24].…”
Section: Epidemiologymentioning
confidence: 99%
“…SCD leg ulcers have been linked to venous incompetence and vasomotor alterations [13,38,39]. Alpha thalassemia trait has been protective [9,29], although this is not always consistent [13,23,40]. Elevated levels of fetal hemoglobin are generally protective [9,29,41], although this has not been true in all studies [33,42].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Indeed, some have suggested that SCA can be split into two sub-phenotypes based on the relative dominance of one or other of these processes in individual patients. [8][9][10] Pulmonary hypertension, a known complication in patients with the hemolytic sub-phenotype of SCD, is thought to be caused by vasculopathy related to the chronic nitric oxide depletion from continuing intravascular hemolysis. 11 Although the markers of SCN are known to predict the presence of pulmonary hypertension, 12 it is still not clear if both conditions share the same pathological process.…”
Section: Introductionmentioning
confidence: 99%
“…11,51,54,55 Much of this work is facilitated by very careful observations of the natural history of disease and by the formation of clinical research networks within and between countries. [56][57][58] Nevertheless, there remains an urgent need to extend these networks more effectively to include the large number of African countries where, so far, there is not only limited detailed prevalence data as discussed above, but also very little information about the clinical features of the disease.…”
mentioning
confidence: 99%